Natural inhibitors of tumor-associated proteases - Magdolen, Ulla (Radiology and oncology (Ljubljana), 2002)
The turnover and remodelling of extracellular matrix (ECM) is an essential part of many normal biological processes including development, morphogenesis,and wound healing. ECM turnover also occurs in severe pathological situations like artherosclerosis, fibrosis, tumor invasion and metastasis. The major proteases involved in this turnover are serine proteases(especially the urokinase-type plasminogen activator/plasmin system),matrix metalloproteases (a family of about 20 zinc-dependent endopeptidases including collagenases, gelatinases, stromelysins, and membrane-type metalloproteases), and cysteine proteases. In vivo, the activityof these proteases is tightly regulated in the extracellular space by zymogen activation and/or controlled inhibition. In the present review, we give an overview on the structure and biochemical properties of important tumor-associated protease inhibitors such as plasminogen activator inhibitor type 1 and type 2 (PAI-1, PAI-2), tissue inhibitors of metalloproteinases (TIMP-1, -2, -3, and -4), and the cysteine protease inhibitor cystatin C. Interestingly, some of these inhibitors of tumor-associated proteases display multiple functions which rather promote than inhibit tumor progression, when the presence of inhibitors in the tumor tissue is not balanced.
Keywords: biokemija; Cistatini; cisteinske proteinaze; Cystatins; Cysteine proteinases; inhibitorji; Metalloproteinases; Neoplasms; Novotvorbe; onkologija; Plasminogen activator inhibitor 1; Plasminogen activator inhibitor 2; Plazminogen aktivator, inhibitor 1; Plazminogen aktivator, inhibitor 2; proteaze; tumor; Urokinase; zgradba